A comparison between expert systems and autonomic computing plus mobile agent approaches for fault management. (2011)
In this article, a revision of literature on application of expert systems to fault management is presented. Then, a new approach, based on the autonomic computing paradigm and mobile agents technology is introduced. The main features of this new approach are compared to equivalent ones of expert systems. Benefits of the schema based on mobile agents are presented.